Building our research administrator workforce as our clinical and translational research programs become increasingly complex - Kayla, Calvo; Jennifer, Phillips; Sandra, Burks; Johnston, Karen C. (Frontiers in Pharmacology, 2023)
Research administrators (RA’s) are critical members of the research workforce. For purposes of this article, research administrators are personnel who support the development, compliance, management, and financial oversight of sponsored research. There are currently very few institutional career development and mentoring programs available to research administrators. Recruitment and retention of quality research administrators has been especially challenging across the country in recent years. In an effort to address this gap in training and to increase recruitment and retention, the integrated Translational Health Research Institute of Virginia (iTHRIV), a collaborative NIH-NCATS funded Clinical Translational Science Award (CTSA) hub, has developed an innovative program of workforce development and mentoring for research administrators. This article provides an overview of one institutional training & development initiative, the Research Administration Program for Training and Resources (RAPTR). RAPTR provides training, resources and mentoring to develop a Community of Practice. The program provides a forum where research administrators can share ideas, practices, and challenges. This manuscript describes the benefits and lessons learned from our early experience in this program. We highlight selected components that may be generalizable to other institutions and describe individualized components, which require local policies and processes.